The Effect of Net Income and Net Cash Flow on Market Capitalization - Heryanti; Supriyanto (Gorontalo Accounting Journal, 2026)
Market capitalization reflects a company’s value from the perspective of investors and serves as an important indicator in assessing growth prospects and overall financial performance. This study aims to examine the effect of net income and net cash flow on market capitalization of companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research employs a quantitative approach using multiple linear regression analysis based on secondary data derived from companies’ annual financial reports. The results indicate that net income has a positive and statistically significant effect on market capitalization, suggesting that higher profitability enhances investor confidence and increases firm value. In contrast, net cash flow shows a positive but statistically insignificant effect on market capitalization, indicating that cash flow information is not the primary consideration for investors in valuing firms during the observation period. Furthermore, the relatively low coefficient of determination suggests that market capitalization is influenced by other factors beyond the variables examined in this study. These findings highlight the importance of profitability as a key determinant of firm value in the capital market.